Research on the optimization of the construction process through the digitalization of construction projects - KOBELCHUK, Oleksandr; KONONCHUK, Roman (Ways to Improve Construction Efficiency, 2025)
The purpose of this study was to investigate the impact of digital technologies on the optimization of the construction process in conditions of unstable financing or lack of resources and to formulate practical recommendations for their effective implementation. The research methodology included an analysis of current trends in the field of digital solutions, in particular, building information modeling (BIM), Internet of Things technologies, artificial intelligence, digital twins and cloud platforms. The possibilities of integrating these technologies to improve the planning, construction and operation of facilities, as well as their impact on increasing the efficiency of resource management, were considered. Real-world case studies were conducted, including the implementation of BIM technology in the ASTON HALL project by DEHAUSS, which confirmed the significant potential of digital technologies. The Crossrail project was also considered, where BIM technologies ensured effective coordination between contractors, as well as digital twins abroad, which are used to manage urban resources. The study showed that BIM technologies contribute to reducing errors in design and construction, improving coordination between project participants and reducing costs. Internet of Things technologies provide real-time monitoring of the condition of construction materials and equipment, which increases safety and reduces the risk of downtime. The use of artificial intelligence allows predicting potential delays, optimizing logistics and automating management processes. The main problems of digitalization of construction remain the high cost of technology implementation, the need for personnel training, difficulties in integrating software platforms and cybersecurity issues. At the same time, benefits such as process automation, increased accuracy of load calculations and energy efficiency, optimization of resource supply and improved control over construction projects confirm the strategic importance of digital solutions in the development of the construction industry. The results of the study showed that a comprehensive approach to the implementation of digital technologies, adaptation of construction processes and effective integration of digital platforms can significantly increase the productivity of construction projects, especially in conditions of unstable supply of construction resources.